2015
DOI: 10.1007/s00170-015-7505-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of filler wire and wire feed speed on metallurgical and mechanical properties of MIG welding–brazing of automotive galvanized steel/5754 aluminum alloy in a lap joint configuration

Abstract: In this research, the galvanized steel with thickness of 2 mm was joined to the 5754 aluminum alloy with thickness of 3 mm by the cold metal transfer MIG welding-brazing process. The effect of the filler wires (AlSi 3 Mn, AlSi 5 , and AlSi 12 ) and wire feed speeds (4.7, 5, and 5.3 m/min) on metallurgical and mechanical properties have been discussed. According to the experimental results, thickness of intermetallic compound (IMC) layer which was formed along the interface during the MIG welding-brazing was va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…The authors found phase layer thickness around 1.3 ~ 2 μm with maximum joint strength of 73 MPa for aluminium to GA sheets 45,46) , while joining with GI sheet exhibited higher joint strength of 210 MPa with phase layer thickness of 0.8 ~ 4.5 μm 7) . Milani et al 47) examined the influence of different filler wires -AA4043, AA4047 and Al-Si3-Mn -on joining of 2 mm thick AA5754 alloy and 3 mm thick GI steel sheets by CMT process. The maximum joint strength was found to be around 188 MPa with the Al-Si3-Mn1 filler wire 47) .…”
Section: Gas Metal Arc Based Joiningmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found phase layer thickness around 1.3 ~ 2 μm with maximum joint strength of 73 MPa for aluminium to GA sheets 45,46) , while joining with GI sheet exhibited higher joint strength of 210 MPa with phase layer thickness of 0.8 ~ 4.5 μm 7) . Milani et al 47) examined the influence of different filler wires -AA4043, AA4047 and Al-Si3-Mn -on joining of 2 mm thick AA5754 alloy and 3 mm thick GI steel sheets by CMT process. The maximum joint strength was found to be around 188 MPa with the Al-Si3-Mn1 filler wire 47) .…”
Section: Gas Metal Arc Based Joiningmentioning
confidence: 99%
“…Milani et al 47) examined the influence of different filler wires -AA4043, AA4047 and Al-Si3-Mn -on joining of 2 mm thick AA5754 alloy and 3 mm thick GI steel sheets by CMT process. The maximum joint strength was found to be around 188 MPa with the Al-Si3-Mn1 filler wire 47) . In another study, Chang et al 48) investigated the effect of AA2319 (Al-6%Cu) and AA5087 (Al-5%Mg) filler wire on joint quality in joining of AA6082 and ultra-high strength steel, both of 4 mm in thickness, by GMA process.…”
Section: Gas Metal Arc Based Joiningmentioning
confidence: 99%
“…In particular, Al-5% or 12% Si or Zn-15% Al are commonly used filler alloys. Dong et al [9], Su et al [10] and Milani et al [11] have shown that a relatively high amount of Si in the filler wire can reduce the diffusion of iron in molten aluminum, resulting in a reduction of the thickness of the IMC layers, and especially of the Al 5 Fe 2 layer.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several studies have reported the miraculous role of Si in preventing the excessive formation of hard and brittle Fe-Al binary intermetallic phases. 27,28 Figure 6 shows the microstructural evolution in the fusion zone (deposited Al-Si-Mn filler) and intermetallic compound layer at the interface of deposited filler-steel. The fusion zone consisted of α-Al matrix and Al-Si eutectic phases at its grain boundaries.…”
Section: Resultsmentioning
confidence: 99%